Association of XRCC1 genetic polymorphism with the risk of thyroid cancer in Indonesia - Harry Nugroho Eko Surniyantoro; Nabilah Adzra Fahlevi; Esa Savitri; Tur Rahardjo; Rita Maliza; Ayu Rosemeilia Dewi; Yustia Tuti; Nastiti Rahajeng; Yanti Lusiyanti; Nur Rahmah Hidayati (Nusantara Science and Technology Proceedings, 2021)
One of the important DNA repair pathways is base excision repair (BER), which plays in the human body to maintain DNA integrity, prevent cancer and DNA damage. X-ray repair cross-complementing group 1 (XRCC1) is the most important DNA repair protein in base excision repair (BER) pathways and has been reported to have a relationship with the risk of developing various cancers. The study was purposed to assess the genetic polymorphism of XRCC1 exon 6 and 10 as a risk factor for thyroid cancer. A total of 90 participants were enrolled in this study, consisted of 30 thyroid cancer patients as a case group and 60 non-cancer patients as a control group. Examination of XRCC1 genotypes was carried out by using Polymerase Chain Reaction-Restriction Fragment Length Polymorphism (PCR-RFLP) method and statistical analysis using a Chi-square test. In this study, we reported the frequency of XRCC1 genetic polymorphism was not significantly different between cancer patients and control groups both in exon 6 and 10, and we predict that these polymorphisms were not a risk factor for thyroid cancer (P-value>0.05). In conclusion, both mutant variants of XRCC1 exon 6 and 10 are not risk factors for thyroid cancer. In further studies, it is necessary to assess genetic polymorphisms in populations with controlled non-genetic factors, such as diet, lifestyle, and environmental factors.